1961
DOI: 10.1084/jem.113.6.981
|View full text |Cite
|
Sign up to set email alerts
|

The Isolated Perfused Bovine Liver

Abstract: The technique of isolated liver perfusion has several unique features as an investigative tool for the study of hepatic physiology and biochemistry. These include the exclusion of non-hepatic tissues, the maintenance of intact cellular membranes, and the ability to control and reproduce more precisely the experimental hepatic environment than is possible in an entire animal. This investigative team has developed an isolated bovine liver peffusion preparation that is reproducible, bacterially sterile, and capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Flow controlled set-ups have been used most often (Chapman et al, 1961;Villeneuve et al, 1996;Grosse-Siestrup et al, 2002b;Zeitlin and Eshraghi, 2002;Dragu et al, 2011), but newer evidence suggests that pressure controlled perfusion improves organ preservation (Mancina et al, 2015). Two strategies may be applied in flow controlled experiments: a low flow or a high flow approach.…”
Section: Perfusatementioning
confidence: 99%
See 3 more Smart Citations
“…Flow controlled set-ups have been used most often (Chapman et al, 1961;Villeneuve et al, 1996;Grosse-Siestrup et al, 2002b;Zeitlin and Eshraghi, 2002;Dragu et al, 2011), but newer evidence suggests that pressure controlled perfusion improves organ preservation (Mancina et al, 2015). Two strategies may be applied in flow controlled experiments: a low flow or a high flow approach.…”
Section: Perfusatementioning
confidence: 99%
“…However, many studies have been successful without the use of antibiotics. One study with a sterile harvesting process and sterile system reported no bacterial contamination for up to 24 hours (Chapman et al, 1961). However, most perfusion experiments are conducted in an unsterile environment.…”
Section: Oxygenmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated liver perfusion has been accomplished in many species, including .the cat, monkey, rabbit (G), and rat. (2O) It has only been recently, however, that perfusion techniques have been consistently satisfactory in larger animals such as the cow or calf (29,30), the pig (51), and the dog. (93) Although the dog is probably the most convenient and cheapest animal f o r perfusion studies, the canine liver has peculiarities which deserve special comment.…”
Section: Isolated Perfusion Of the Livermentioning
confidence: 99%